ANALISIS KEMAMPUAN SISWA DALAM MENEMUKAN NILAI MORAL PADA CERITA RAKYAT JAWA GUNUNG TUGEL MATA PELAJARAN BAHASA JAWA KELAS IV MI TERPADU AL MABRUR TAWANGSARI SUKOHARJO TAHUN 2024/2025 - Rahmat, Basuki; Nurhidayati, Indah; Praptiningsih, P (MAMBA'UL 'ULUM, 2025)
Difficulty in comprehending Javanese, which has a rich vocabulary and many expressions, makes it challenging for students to find the moral values contained within the text. Therefore, the objective of this research is to determine the students' ability to find moral values and to identify the factors influencing their ability to do so in the Javanese folk tale, "Gunung Tugel," for 4th Grade Javanese Language subject. This study uses a descriptive qualitative approach. Data collection techniques involved observation, interviews, and documentation. Data validity was checked using a credibility test with triangulation, utilizing other sources outside the data for cross-checking purposes. The data analysis technique employed the Miles and Huberman model, consisting of Data Reduction, Data Display, and Verification. The results indicate that the students' ability to find moral values in the "Gunung Tugel" story is low. This is reflected in their inability to identify the inherent moral values. Students tend to view the story merely as entertainment without delving into the underlying meaning. This limitation suggests that the development of students' intellectual capacity in evaluating and reflecting on moral values from narrative texts is not yet optimal. Influencing factors include: minimal student interest and motivation towards folk tales, the perception that folk tales are only entertainment, the "Gunung Tugel" story being considered less interesting by some students, and constraints in understanding the language of the story, which becomes the main obstacle in finding the moral values.